Does Intellectual Capital Alleviate Bank Earnings Management? New Findings from Vietnamese Context - Lu, Chi Huu (Asian Academy of Management Journal of Accounting and Finance, 2025)
Being “black boxes” in an economy, consequences resulting from manipulation of number reporting in banks has kept the spotlight of central banks worldwide for decades. Accordingly, many efforts that aim to enhance bank financial information transparency have been studied and proposed. In astonishment, despite the widely demonstrated influential role of intellectual capital in banking operations, the linkage between this factor and bank earnings management is largely unexplored. Motivated by this fact, the study makes the first endeavour to pinpoint how intellectual capital can assist banks in reducing earnings management. By employing the extended-VAIC model rather than the traditional measure, the panel data analysis based on the research sample of 26 Vietnamese banks from 2006 to 2020, with the support of different econometric methods shows that increasing intellectual capital will demotivate banks to be involved in earnings management. Also, three elements of intellectual capital: structural capital, relational capital and capital employed play a crucial role in alleviating bank earnings management. By contrast, the last element, human capital, does not yet help banks preclude financial misrepresentation, especially in small banks. These findings will be of special interest to bank regulators and managers in Vietnam and perhaps, other emerging economies.